2011
DOI: 10.1161/hypertensionaha.110.168484
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Venous Sampling

Abstract: Abstract-In patients with primary aldosteronism, adrenal venous sampling is helpful to distinguish between unilateral and bilateral adrenal diseases. However, the procedure is technically challenging, and selective bilateral catheterization often fails. The aim of this analysis was to evaluate success rate in a retrospective analysis and compare data with procedures done prospectively after introduction of measures designed to improve rates of successful cannulation. Patients were derived from a cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 204 publications
(84 citation statements)
references
References 28 publications
2
78
2
2
Order By: Relevance
“…Previous studies determined the clinical impact of adrenalectomy chosen based on CT alone or CT plus AVS (5,14,(17)(18)(19). Those authors reported that the reduction in BP, number of hypertensive medications, plasma aldosterone, and potassium normalization at follow-up were equivalent in the two groups and concluded that CT could be used to diagnose nodules >10 mm reliably and that AVS should be used when CT is normal or both adrenal glands are abnormal (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies determined the clinical impact of adrenalectomy chosen based on CT alone or CT plus AVS (5,14,(17)(18)(19). Those authors reported that the reduction in BP, number of hypertensive medications, plasma aldosterone, and potassium normalization at follow-up were equivalent in the two groups and concluded that CT could be used to diagnose nodules >10 mm reliably and that AVS should be used when CT is normal or both adrenal glands are abnormal (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…6,11,12 Moreover, AVS is an invasive technique that is not well standardized between centers and heavily depends on the expertise of the interventional radiologist. 13,14 AVS furthermore requires the use of contrast agents in a patient population that often experiences impaired renal function. 15 To date, proposed clinical prediction scores cannot replace AVS.…”
Section: Hypertensionmentioning
confidence: 99%
“…AVS was carried out after 2-3 h of resting in supine position between 0800 and 1200 h as described previously (17). Selective AVS was assumed for the purpose of this study, if cortisol of the adrenal vein was 100% higher than cortisol in the inferior vena cava (cortisol in adrenal vein/cortisol in inferior vena cava R2.0).…”
Section: Design and Patientsmentioning
confidence: 99%